Variation in Susceptibility to Bacillus thuringiensis Toxins among Unselected Strains of Plutella xylostella - González-Cabrera, J. (American Society for Microbiology, 2001)
So far, the only insect that has evolved resistance in the field to Bacillus thuringiensis toxins is the diamondback moth (Plutella xylostella). Documentation and analysis of resistant strains rely on comparisons with laboratory strains that have not been exposed to B. thuringiensis toxins. Previously published reports show considerable variation among laboratories in responses of unselected laboratory strains to B. thuringiensis toxins. Because different laboratories have used different unselected strains, such variation could be caused by differences in bioassay methods among laboratories, genetic differences among unselected strains, or both. Here we tested three unselected strains against five B. thuringiensis toxins (Cry1Aa, Cry1Ab, Cry1Ac, Cry1Ca, and Cry1Da) using two bioassay methods. Tests of the LAB-V strain from The Netherlands in different laboratories using different bioassay methods yielded only minor differences in results. In contrast, side-by-side comparisons revealed major genetic differences in susceptibility between strains. Compared with the LAB-V strain, the ROTH strain from England was 17- to 170-fold more susceptible to Cry1Aa and Cry1Ac, respectively, whereas the LAB-PS strain from Hawaii was 8-fold more susceptible to Cry1Ab and 13-fold more susceptible to Cry1Da and did not differ significantly from the LAB-V strain in response to Cry1Aa, Cry1Ac, or Cry1Ca. The relative potencies of toxins were similar among LAB-V, ROTH, and LAB-PS, with Cry1Ab and Cry1Ac being most toxic and Cry1Da being least toxic. Therefore, before choosing a standard reference strain upon which to base comparisons, it is highly advisable to perform an analysis of variation in susceptibility among field and laboratory populations.